La grande propriété foncière bruxelloise au XIXe siècle - Louise Babar (Belgeo)
This article follows the various steps that lead to the reconstitution of the ownership estates in the Brussels area in 1860, using the data of old land registries in modern GIS. The spatial distribution of landed estates is examined, as well as the social composition of land owners and the origins of properties. This allows one to link certain characteristics of the spatial and social structure of land ownership to political events unfolding from the end of the 18th until the end of the 19th century. Highlighting either the permanence of the old social-spatial inherited organisation, or more recent changes following the fall of the old regime, the results point out the dynamic of social recomposition happening in the elite group, while also showing that social-spatial structures follow strong spatial auto-reproduction mechanisms.